Questioning the Customary Inheritance Law After Law No. 3 of 2006 about Religious Jurisdiction - Adhi, Yuli Prasetyo; Triyono, Triyono; Muhyidin, Muhyidin (Indonesian Journal of Advocacy and Legal Services, 2021)
Customary inheritance dispute might occur when the heirs cannot reach agreement between divisions of property or during inheritance law point which will be used. Indonesia acknowledges 3 existing inheritance laws which are western civil inheritance law, Moslem's inheritance law, and customary inheritance law. Legal action of inheritance law is usually resolved by deliberation but if there is no agreement reached between these processes, therefore court mechanism can be used to make law suit and dispute resolution. UU No 3 of 2006 about religious jurisdiction is a legal product that is issued to provide improvement (Amendment) against UU No 7 of 1989 about religious jurisdiction. UU No 3 of 2006 is giving significant impact against the existence of custom inheritance law in Indonesia. Before this constitution is created, religious jurisdiction can accept customary inheritance disputes for Moslem people according to the criteria which have been stated in UU No 7 of 1989. Since UU No 3 of 2006 is created, therefore customary inheritance law, even though the heirs are Moslem, must follow the district court mechanism. This will provide increasingly narrow space for the existence of customary law in the future. This program is held in Pati, Central Java, where custom inheritance law still exists and is being used in Pati community. Dissemination and harmonization regarding customary law is important to maintain sustainability and existence of customary law in Indonesia.